The effects of intermittent fasting on cardiovascular health of prediabetes and Type 2 diabetes mellitus (T2DM) patients: a systematic review - Afdzal Rasif, Muhammad Naif Hafizin; Nazri, Amirah Farhana; Soe, May Khin (Malaysian Pharmacists Society, 2023)
Background: Type 2 diabetes mellitus and prediabetes are showing an increasing number of cases and are predicted to keep increasing over the years. Both conditions have a 2-3-fold increased risk of developing cardiovascular diseases. Intermittent fasting is one of the forms of dietary intervention being practiced in preventing and managing these conditions and their associated complications. There are many reported benefits of intermittent fasting for health, but no specific studies discussed regarding the effect of this practice on cardiovascular health of these patients. Objective: This study is aiming to systematically review the benefits of intermittent fasting on cardiovascular health of these groups of patients. Methods: This systematic review followed the guideline of PRISMA and was registered at PROSPERO with the registration number of CRD42022378349. A systematic literature search was conducted in PubMed, Scopus, Cochrane Library, Google Scholar and by using snowball technique. The articles retrieved were independently screened by two authors against the eligibility criteria in stages of title, abstract, and full text. The risk of bias in the included studies were assessed independently by two authors using the Joanna Briggs Institute critical appraisal checklist. Data from all the included articles were extracted using a predetermined template. Results: Twelve studies were included in this study. Six studies recorded a low risk of bias while the other six studies had moderate risk of bias. Three studies recorded significant reduction in both systolic and diastolic blood pressure, and 3 studies showed significant improvement in the lipid profiles at the end of intervention. Conclusion: Intermittent fasting is beneficial for cardiovascular health of prediabetes and type 2 diabetes mellitus patients mainly by improving both systolic and diastolic blood pressure and the lipid profiles. Randomized controlled trials that investigate specifically the benefits of this practice on the cardiovascular health of these populations are needed to confirm the findings.